Pertumbuhan benih ikan mas, Cyprinus carpio, yang diberi pakan dengan dosis berbeda pada kolam pekarangan dengan sistim resirkulasi - Jasansong, Kalfianus; Salindeho, Indra R. N.; Kreckhoff, Reni L. (e-Journal BUDIDAYA PERAIRAN, 2020)
The research was aimed to find out the optimum dose of feeding regime             to ensure the maximum growth of carp-seeds, Cyprinus carpio, reared in backyard pond with recirculation system. The experiment was carried out in Randomized Block Design with 3 different dose of feeding regimes as treatments, which were 3%, 4% and 5% of the total body weight per day.  Each treatment was triplicate and each repetition functioned as group of fish with different weight.  There were 3 groups which were, fish weighing 1.5–2.4 gram (Group-1), fish weighing 2.5 – 3.4 gram (Group-2) and fish weighing 3.5 – 4.8 gram (Group-3).  Each experimental unit was composed of 8 tested fish, placed in a netting-cage bag measuring 60×30×60 cm (l×w×h) with a mesh-size of 4 mm. Each group was composed of 24 tested fish, hence there were 72 tested fish in total.  Fish were fed twice a day at 07:00 and 17:00.  Tested fish were weighed every week, and the fish weight data were converted into FCR, absolute, relative and daily growth rate. Data were statistically analyzed using JMP statistic-program.  The results showed that, there was no significant difference in absolute, relative and daily growth rate among fish fed 3%, 4% and 5% of total body weight per day.   The best FCR was performed by fish fed 3% of total body weight per day.   Hence, this experiment result suggests that, carp reared in backyard pond with recirculation system should be fed with a dose of 3% of the total body weight each day, as fish might grow well and at the same time the amount of uneaten food, feces and metabolic wastes is minimized at this dose of feeding.